A case displaying the importance of JAK1 and JAK2 gene transcription in antifungal defense against coccidioidomycosis - Priessnitz, Jennifer K.; Colore, Taylor; Nicolasora, Nelson (Frontiers in Medicine, 2025)
This case report explores the consequences of ruxolitinib via inhibition janus kinase 1 (JAK1) and JAK2 pathways in the context of fungal defense in a patient diagnosed with pulmonary coccidioidomycosis during ruxolitinib therapy for polycythemia vera. The patient experienced a relapse of pulmonary coccidioidomycosis after antifungal treatment was discontinued while continuing ruxolitinib use. This case illustrates the heightened risk of discontinuing antifungal therapy in endemic regions, emphasizing the critical need for continued monitoring. Furthermore, this case underscores the vital role of the JAK1 and JAK2 signaling cascade, particularly the interferon-gamma (INF-γ)-JAK1 and JAK2-signal transducer and activator of transcription 1 (STAT) axis, in antifungal defense. Recent studies have revealed that the loss of function in JAK1 (but not JAK2), leads to impaired macrophage activation and reduced T-helper 1 (Th1) cell responses, thereby compromising the body's ability to fight off dimorphic fungi, such as Coccidioides. Other proposed fungal immune mechanisms in the JAK-STAT pathway are discussed. Clinicians tailoring JAK inhibitor treatment options for patients must be aware of the INF-γ-JAK1-STAT pathway's pivotal role in antifungal defense.